Pengembangan E-Book Berbasis Media Video Pada Materi Konstruksi Jalan dan Jembatan Kelas XI Desain Pemodelan dan Informasi Bangunan - Fajar Maulana; Wahyu Dwi Mulyono (Jurnal Kajian Pendidikan Teknik Bangunan, 2025)
Abstract The quality of education can be improved through learning activities carried out by educators at schools. Thus, educators have a major role in realizing effective learning activities. Learning activities can take place effectively and smoothly if assisted by supporting facilities and infrastructure, an example of facilities and infrastructure that can help learning activities is the existence of learning media. This research is motivated by several problems in the field, one of which is that the learning media used is still limited and the difficulty of students' understanding to visualize road and bridge construction objects, therefore the media that can be applied is video-based e-book teaching materials.The aim of this research is to developing video-based e-book learning media in road and bridge construction materials for class XI Design students Modeling and Building Information for SMK Negeri 1 Kediri. Model this research uses the ADDIE model with stages analysis, planning stage, development stage, stage implementation and evaluation stages. This research is limited to implementation stage to see validity and practicality video-based e-book learning media through validation and product testing. Validation consistan of two validators viz media validation, material validation as well as a student response to the effectiveness of using e-book among student. In this research the results Student learning will be known by giving questions to them students, the trial of this product was limited to only 31 class XI Student Modeling Designe and Building Information for SMK Negeri 1 Kediri as a respondent. Data collection techniques us questionnaire and test menthods. Product validation feasibility results from media expert validator gave an assessment of 4,08 with “Good” category, while the material expert validator provided an assessment og 4,7 in the “Very Good” outcomes students after using the e-book were 29 out of 31 students declared “completed learning” of achieved a score above the KKM with a classical completion percentage of 93,5%. The results of student responses after using the video based e-book can be categorized as “Very Good” with a percentage of 87,5%. Keywords: Development, E-book, Video, Road and Bridge Construction.